2015
DOI: 10.1002/14651858.cd003417.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Group based diabetes self-management education compared to routine treatment, waiting list control or no intervention for people with type 2 diabetes mellitus

Abstract: Group based diabetes self-management education compared to routine treatment, waiting list control or no intervention for people with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 297 publications
0
8
0
Order By: Relevance
“… 20 The same is true for research on the characteristics of those who would choose to enroll in such interventions. 20 Work by Steinsbek et al 21 and Galagher et al 22 showed that there was little difference between baseline characteristics of participants in group versus standard treatment modalities. However, current literature suggests that patients’ preference for a treatment type for obesity or NCDs in general may be influenced by factors such as age, gender, cultural perceptions, health status, access to quality healthcare and practical difficulties.…”
Section: Introductionmentioning
confidence: 99%
“… 20 The same is true for research on the characteristics of those who would choose to enroll in such interventions. 20 Work by Steinsbek et al 21 and Galagher et al 22 showed that there was little difference between baseline characteristics of participants in group versus standard treatment modalities. However, current literature suggests that patients’ preference for a treatment type for obesity or NCDs in general may be influenced by factors such as age, gender, cultural perceptions, health status, access to quality healthcare and practical difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…While diabetes self-management education (DSME) and diabetes self-management support (DSMS) programmes have historically been defined as separate entities [5], recently Beck and colleagues [6] Previous DSMES programmes have demonstrated enhanced coping [7], empowerment and selfefficacy [8], improved quality of life (QoL) [9][10][11][12][13] and reduced rates of depression [14,15] and diabetes-related distress [16,17] among individuals with type 2 diabetes (T2DM). Improved adherence to diet and physical activity targets [18] and a reduction in glycosylated haemoglobin (A1C) [9,16,[19][20][21][22][23][24][25] may also limit the onset and severity of diabetes complications [26,27] for individuals receiving DSMES.…”
Section: Diabetes Self-management Education and Supportmentioning
confidence: 99%
“…It has been found that more hours of education (19 to 52 hours) spread over a period of 6 to 10 months or with many sessions (6 to 10 sessions) tended to do better than education with shorter durations [14]. Other studies report a higher effect in education that is compact with meetings closely grouped together [13].…”
Section: Interactive Learningmentioning
confidence: 99%
“…Other studies report a higher effect in education that is compact with meetings closely grouped together [13]. One systematic review reported that education delivered by several educators may improve the effect of education [43], while another review found that only one educator tended to do better than having a group of educators in the educations [14].…”
Section: Interactive Learningmentioning
confidence: 99%
See 1 more Smart Citation